Functional dissociation between action and perception of object shape in developmental visual object agnosia. (March 2016) - Freud, Erez; Ganel, Tzvi; Avidan, Galia; Gilaie-Dotan, Sharon
Abstract: According to the two visual systems model, the cortical visual system is segregated into a ventral pathway mediating object recognition, and a dorsal pathway mediating visuomotor control. In the present study we examined whether the visual control of action could develop normally even when visual perceptual abilities are compromised from early childhood onward. Using his fingers, LG, an individual with a rare developmental visual object agnosia, manually estimated (perceptual condition) the width of blocks that varied in width and length (but not in overall size), or simply picked them up across their width (grasping condition). LG's perceptual sensitivity to target width was profoundly impaired in the manual estimation task compared to matched controls. In contrast, the sensitivity to object shape during grasping, as measured by maximum grip aperture (MGA), the time to reach the MGA, the reaction time and the total movement time were all normal in LG. Further analysis, however, revealed that LG's sensitivity to object shape during grasping emerged at a later time stage during the movement compared to controls. Taken together, these results demonstrate a dissociation between action and perception of object shape, and also point to a distinction between different stages of the grasping movement, namely planning versus online control. Moreover, the present study implies that visuomotor abilities can develop normally even when perceptual abilities developed in a profoundly impaired fashion.